Spatial Analysis of Land Prices in Serpong District, South Tangerang City Based on Grographic Information Systems - Anisa Frismadhanti; Lili Somantri; Iwan Setiawan (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2020)
Serpong District is a sub-district of the City of South Tangerang with an area of ​​24.04 Km2. The purpose of this research is to identify the things that affect the distribution of land price levels and provide visual information about the boundaries of each area of ​​land price levels in Serpong District. Data collection methods in the form of interpretation and literature study methods. Data analysis methods used in this study used map interpretation techniques, the distance method (buffer), the scoring method (scoring) and the overlapping method (overlay). The variables used are land use, positive land accessibility, negative land accessibility and intensity of completeness of public facilities. The results showed that, the level of land prices in the District of Serpong, South Tangerang City was divided into five classes namely, very high, high, medium, low and very low. The level of land prices is very high in the Districts of Serpong and Rawabuntu. The level of land prices is very low in the District of Lengkong Gudang.